Enhancing Hydrogen Generation using CdS-modified TiO2 Nanotube Arrays in 2,4,6-Trichlorophenol as a Hole Scavenger - Ratnawati Ratnawati; Slamet Slamet; Farah Diba Toya; Satrio Kuntolaksono (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Nowadays, the lack of renewable energy such as hydrogen, and other environmental issues are problems that must be resolved. 2,4,6-Trichlorophenol (2,4,6-TCP) is classified as a recalcitrant pollutant due to its carcinogenic properties, high toxicity, and dangers to the environment therefore it needs to be eliminated. Hydrogen production using organic pollutant (2,4,6-TCP solution) as a hole scavenger on CdS-TiO2 nanotube arrays photocatalyst (TNTA-CdS) has been investigated at various CdS loading on TNTA and the initial concentration of 2,4,6-TCP. The TNTA sample was prepared by anodization and followed by an electrodeposition method to decorate CdS on TNTA. The H2 which was generated by reduction H+ and the 2,4,6-TCP removal was performed simultaneously by photocatalysis with TNTA-CdS as photocatalyst. The mole ratio of CdCl2:CH3CSNH2 as precursors of CdS deposited on TNTA (CdS loading) were 0.1:0.06, 0.2:0.12, and 0.4:0.24 and the initial concentration of 2,4,6-TCP were 10, 20 and 40 ppm. Meanwhile, the photocatalytic performance of the variations in CdS loading on TNTA and initial concentration of 2,4,6-TCP toward hydrogen generation was investigated in a photoreactor for 240 minutes under visible light irradiation with a mercury lamp as a photon source. The CdS decorating on TNTA was confirmed by SEM, EDX, and X-ray diffraction (XRD) characterization. According to the UV-Vis and XRD analysis, the TNTA-CdS samples have bandgap energies in the range of 2.71 - 2.89 eV and comprise a 100% anatase phase. Based on the photocatalysis results, the optimum composition of CdS loading is 0.2:0.16 (TNTA-CdS-2) which produced the highest total hydrogen (2.155 mmol/g) compared to the other compositions and produced 1.5 times higher compared to TNTA at 40 ppm of 2,4,6-TCP.